An Exosome‐Based Vaccine Platform Imparts Cytotoxic T Lymphocyte Immunity Against Viral Antigens. Issue 4 (24th March 2018) - Anticoli, Simona; Manfredi, Francesco; Chiozzini, Chiara; Arenaccio, Claudia; Olivetta, Eleonora; Ferrantelli, Flavia; Capocefalo, Antonio; Falcone, Emiliana; Ruggieri, Anna; Federico, Maurizio
Abstract : Exosomes are 50–150 nm sized nanovesicles released by all eukaryotic cells. The authors very recently described a method to engineer exosomes in vivo with the E7 protein of Human Papilloma Virus (HPV). This technique consists in the intramuscular injection of a DNA vector expressing HPV‐E7 fused at the C‐terminus of an exosome‐anchoring protein, that is, Nef mut, the authors previously characterized for its high levels of incorporation in exosomes. In this configuration, the ≈11 kDa E7 protein elicited a both strong and effective antigen‐specific cytotoxic T lymphocyte (CTL) immunity. Attempting to establish whether this method could have general applicability, the authors expanded the immunogenicity studies toward an array of viral products of various origin and size including Ebola Virus VP24, VP40 and NP, Influenza Virus NP, Crimean–Congo Hemorrhagic Fever NP, West Nile Virus NS3, and Hepatitis C Virus NS3. All antigens appeared stable upon fusion with Nef mut, and are uploaded in exosomes at levels comparable to Nef mut . When injected in mice, DNA vectors expressing the diverse fusion products elicited a well detectable antigen‐specific CD8 + T cell response associating with a cytotoxic activity potent enough to kill peptide‐loaded and/or antigen‐expressing syngeneic cells. These data definitely proven both effectiveness and flexibility of this innovative CTL vaccine platform. Abstract : The authors recently described the proof‐of‐principle around a novel generation of vaccines based on intramuscular injection of a DNA molecule expressing the antigen of interest fused with a protein they identified for its ability to accumulate into exosomes, that is, nanovesicles constitutively released by all cell types. The expression in muscle cells of such DNA vectors generates the release of exosomes inducing a strong cellular immune response against the products they incorporate. Through immunogenicity tests in animals, in this study the authors demonstrate that this novel vaccine platform can be applied on a wide range of viral proteins, hence opening the way toward its use for the generation of cellular immunity against any kind of antigen.